Macroeconomic Crisis and Individual Firm Performance: The Mexican Experience - Karen Watkins; Dick van Dijk; Jaap Spronk (Tinbergen Institute, 2004)
This paper considers financial, operational, solvency, and performance ratios, in order to detect when there were balance sheets' variations related to the 1994 Mexican currency crisis. Quarterly results for 88 non-financial Mexican companies that survived the crisis are used, and tests for structural change are performed. Findings show that generally firms' balance sheets deteriorated between the fourth quarters of 1993 and 1995, which points the possibility of corporate roots of the macroeconomic crisis. Although in most cases firms' balance sheets improved after the crisis, the recovery was partial and gradual, and overall this episode was prejudicial even for surviving companies.
Keywords: F3; G0; G3; 330; financial crisis; firm-level data; Währungskrise; Bilanz; Unternehmenserfolg; Mexiko; Finanzkrise